The effectiveness of tofu liquid waste for growing Chlorella sp. - Hotma Br Sidabutar; M. Hasbi; Budijono ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Tofu liquid waste is rich in micro and macro nutrients that can be used to grow microalgae such as Chlorella sp. To understand the effectiveness of the waste as a medium to grow Chlorella sp., a study was conducted from March – May 2016. Different amount of waste was mixed with aquadest, there were P0 (0% waste), P1 (65% waste), P2 (75% waste) and P3 (85% waste) were used as nutrient source for the microalgae that were cultured for 20 days. Parameters measured were the abundance and biomass of Chlorella sp., nitrate and phosphate concentration, CO2, pH, and temperature. Results shown that the best growth of Chlorella sp. was in the P3, the abundance was 18.46 x 106 cells/ml and biomass was 0.70 g/l. The growth of Chlorella sp. was able to reduce the nitrate and phosphate concentration, from 7.09 to 0.23 mg/l and from 1.04 to 0.40 mg/l respectively. This fact indicates that the nutrients have been used for growing the microalgae. Based on data obtained, it can be concluded that the tofu liquid waste can be used as medium for growing Chlorella sp. Keywords: Tofu liquid waste, nutrient, medium, Chlorella sp.